Pasantía con Equipo de Acompañamiento y Representación Común (2022)
The possibility of having completed internships in an entity such as the Commission Colombiana de Juristas gave me a lot of growth as a professional every time I I help to expand my knowledge in the topics that it covers, such as Law Humanitarian, International Human Rights Law, Special Jurisdiction for Peace, Transitional Justice and History of our internal armed conflict and how it is has developed in the country. This allows me to know more in depth topics that are latent today and that are very important to treat our armed conflict.